Myanmar - Stads, Gert-Jan; San, Cho Cho; Khing, Aeintjue Kay; Omot, Norah; Pham, Nguyen Thi; Nin-Pratt, Alejandro; Boughton, Duncan; Win, Su Su; Kyi, Thanda (International Food Policy Research Institute, 2019)
Despite a considerable increase in agricultural research spending in recent years, Myanmar is still seriously underinvesting. At just 0.06 percent in 2017, the country’s agricultural research intensity ratio (that is, spending as a share of AgGDP) is one of the lowest in the world. The number of agricultural researchers has grown steadily over time, as has the average qualification level of researchers. The majority of researchers are crop scientists, however, leaving other important areas (notably livestock and fisheries) severely underresearched. ADS was launched in 2018 to address many of the challenges that Myanmar’s national agricultural research system is facing, including severe underinvestment, organizational fragmentation, limited geographic dispersion of research, neglected research domains, and an ineffective extension system.